Gas‐permeation performance of metal organic framework/polyimide mixed‐matrix membranes and additional explanation from the particle size angle. Issue 10 (14th November 2017) - Duan, Cuijia; Jie, Xingming; Zhu, Haitao; Liu, Dandan; Peng, Weiming; Cao, Yiming
ABSTRACT: With MOFs of Cu3 (BTC)2 and ZIF‐8 as the dispersed phases and four polyimides with CO2 permeabilities ranging from 1.36 to 564 barrer as the continuous phase, the influence of metal organic frameworks on the gas‐separation properties of mixed‐matrix membranes (MMMs) was investigated. The results show that the gas permeabilities of all of the prepared MMMs greatly increased and even largely exceeded the predicted value of the Bruggeman model; for example, with the same Cu3 (BTC)2 loading of 21.3 vol %, the O2 permeability increase rate of our prepared Cu3 (BTC)2 /Matrimide 5218‐20 MMMs was 2.26 times, whereas that predicted by the Bruggeman model was only 1.05 times. In addition, when the gas permeability of the polymeric phase was far lower than the dispersed phase of ZIF‐8 or Cu3 (BTC)2 compared with ZIF‐8, which had a particle size ( R ) around 150 nm, Cu3 (BTC)2 of 5–15 µm showed a little better enhancing effect on the gas‐permeation performance of the MMMs. In addition to the properties of the dispersed and continuous phases, we speculated that the ratio between R of the dispersed phase to the membrane thickness ( L ) played an important role for MMMs; the larger R / L was, the greater the gas permeability of the MMMs was. This speculation was initially evidenced by the ZIF‐8/ODPA/TMPDA‐20 MMMs with different L s. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45728. Abstract :